Principles of sustainable development in traditional local architecture Hassan Fathi Works as a Case Study - Alobaidi, Maysaa M. (Sulaimani Journal for Engineering Sciences, 2019)
Sustainable development is the most common concept in societies through the optimal utilization of available resources, whether human, physical or natural, in an effective, balanced, environmental, urban, human, economic and even social way to ensure their continuity and sustainability without wasting the gains of future generations. In the coming generations, so sustainable development represents all aspects of human life and its needs, including the urban environment as one of the most important aspects of application of environmental dimensions, social and economic and even technology. However, what seems new is, in fact, a concept rooted in our traditional urban environment. This is through the appropriateness of elements and vocabulary and the application of the values and concepts of our society environmentally, economically and socially. Thus, ensure that its capabilities are preserved for future generations. Hence, the importance of this research can be drawn through the knowledge of the principles of sustainable development and its applications in traditional local architecture. This research was chosen by architect Hassan Fathi. This study aimed to build a conceptual framework for the principles of sustainable development and the possibilities of employing them in the traditional local production of previous studies. The research, then, went on to test them theoretically and practically on a selected group of Hassan Fathi's works to approach the mechanisms that enable the researches of this study to promote sustainable design to enhance local contemporary architectural product.
Keywords: sustainable development; sustainable architecture; traditional architecture; Hassan Fathi